Penitipan Anak di Panti Asuhan Aisyiyah Kota Payakumbuh Pasca Perceraian Perspektif Konsep Maslahah - Fidiatul Fadillah; Sofia Ridha (Lembaga Yasin AlSys, 2026)
Divorce often gives rise to subsequent family problems, particularly those related to child care. In the concept of hadhanah in Islamic law, responsibility for child care after divorce remains with the parents. However, in practice, placing children in an orphanage has emerged as an alternative form of care when parents face economic, social, or psychological limitations. This study aimed to explain the practice of post-divorce child placement at the Aisyiyah Orphanage in Payakumbuh City and to analyze it from the perspective of the concept of maslahah in Islamic law. This study employed field research using a descriptive-analytical qualitative approach. Data were obtained through observation, interviews with orphanage administrators and the parents of foster children, and documentation, and were then analyzed inductively based on the concepts of maslahah and maqashid al-sharia. The results showed that the practice of child placement at the Aisyiyah Orphanage was carried out through systematic administrative procedures, including form completion, family surveys, and interviews. The main reasons for placing children in the orphanage included economic hardship, the inability of single parents to care for their children, the formation of a new family, and the inability of the extended family to provide care. From the perspective of maslahah, this practice may be justified because it provides benefits for the child, such as the fulfillment of basic needs, access to education, and character development through a semi-pesantren caregiving system. Thus, child placement in an orphanage may be regarded as a form of maslahah hajjiyah that is consistent with the objectives of maqashid al-sharia in safeguarding life and progeny. This study confirms that the concept of maslahah may serve as a normative foundation for assessing alternative caregiving practices after divorce, as long as the best interests of the child remain the primary consideration.